2021
DOI: 10.1038/s41467-021-22382-y
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the reactivity of alkoxyl radicals from 1,5-hydrogen atom transfer to 1,2-silyl transfer

Abstract: Controlling the reactivity of reactive intermediates is essential to achieve selective transformations. Due to the facile 1,5-hydrogen atom transfer (HAT), alkoxyl radicals have been proven to be important synthetic intermediates for the δ-functionalization of alcohols. Herein, we disclose a strategy to inhibit 1,5-HAT by introducing a silyl group into the α-position of alkoxyl radicals. The efficient radical 1,2-silyl transfer (SiT) allows us to make various α-functionalized products from alcohol substrates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Recently, we reported that radical 1,2-silyl transfer (1,2-SiT) of alkoxyl radicals could be favored over 1,5-HAT and β-carbon elimination in some cases. , We wondered whether alkoxyl radicals A could still undergo 1,2-SiT to generate ketyl radicals B , instead of generating radicals C through intramolecular olefin addition (Scheme b). If this hypothesis works, the carbon radical B could add to the alkene to generate carbon radicals D or D′ .…”
mentioning
confidence: 99%
“…Recently, we reported that radical 1,2-silyl transfer (1,2-SiT) of alkoxyl radicals could be favored over 1,5-HAT and β-carbon elimination in some cases. , We wondered whether alkoxyl radicals A could still undergo 1,2-SiT to generate ketyl radicals B , instead of generating radicals C through intramolecular olefin addition (Scheme b). If this hypothesis works, the carbon radical B could add to the alkene to generate carbon radicals D or D′ .…”
mentioning
confidence: 99%
“…In addition, many oximes and oxime ethers show antifungal, antibacterial, or antitumor activity (Scheme B) . For these reasons, the development of efficient methods for the synthesis of oxime ethers has attracted considerable attention from chemists . Recently, the Kim group reported innovative work involving radical coupling reactions between sulfonyl-containing oxime ethers and alkyl halides to afford oxime ethers .…”
mentioning
confidence: 99%
“…The generation of more stable secondary carbon radical 10a is favorable over primary carbon radical 10b . The intramolecular addition of 10a to the acylsilane would generate alkoxyl radical 11 , followed by radical Brook rearrangement to generate 12 66 76 . Giese-type addition of 12 to allylic sulfone would generate intermediate 13 , which would eliminate PhSO 2 radical and product 3a to close mechanism cycle.…”
Section: Resultsmentioning
confidence: 99%